Photonic coupled systems between on-chip integrated microresonator and core-shell nanoparticle. Issue 1728 (30th January 2015) - Xiong, Y.; Pignalosa, P.; Yi, Y.
ABSTRACT: We have numerically investigated the unique effects of the core-shell nanoparticles on the integrated micro disk resonator. By attaching the core-shell nanoparticle to the disk resonator with gold core and polymer shell, the coupling between the disk resonator and the core-shell nanoparticle results in shift of the resonance wavelength of the disk resonator, depending on the core size/shell thickness of the nanoparticle. An ' invisibility ' phenomenon found from the coupled core-shell nanoparticle and integrated disk resonator system is emphasized: at certain core size/shell thickness ratio, compared to the original resonance wavelength without core-shell nanoparticle, there is almost no resonance wavelength shift observed. The dependence of the position and number of core-shell nanoparticles is also discussed. Future studies on this coupled photonic systems will stimulate wide variety of applications.